PENGARUH KARAKTERISTIK MINERALOGI TERHADAP KAPASITAS TUKAR KATION ZEOLIT ALAM PACITAN, JAWA TIMUR - Wawan Budianta; I Wayan Warmada; Makruf Nurudin (KURVATEK, 2023)
The study aimed to investigate the influence of mineralogical and chemical composition on the cation exchange capacity of natural zeolite obtained from Pacitan, East Java. Ten natural zeolite samples were analyzed for mineralogical and chemical composition and cation exchange capacity. The result of the study showed that the natural zeolite samples have a mordenite-type mineral in dominant, with the percentage in vary between 32% to 38%. Based on chemical analysis, the natural zeolite samples consist of SiO2 ranging from 61% to 66% and Al2O3 ranging from 9% to 11%, which are then calculated to obtain for Si/Al ratio. The value of cation exchange capacity obtained ranges from 70 meq/100 g to 91 meq/100 g, with 82 meq/100 g on average. This variation was most probably influenced by the difference in zeolite mineral type presence and other minerals. Moedenite mineral type was suspected as the most dominant, which influenced the cation exchange capacity value obtained in this study. The cation exchange capacity of the samples gives a positive correlation to the content of the mordenite mineral, total microporous mineral, and Si/Al ratio. The result of the study is expected to contribute to the information on the natural zeolite in the area for agricultural and environmental fields.